United Nations Commission on International Trade Law; T24 - United Nations (United Nations, 1995)
This book consists of three parts: Part one contains the Commission's report on the work of its twenty-seventh session. In part two most of the documents considered at the twenty-seventh session of the Commission are reprodeced. Part three contains the UNCITRAL Model Laww on Procurement of Goods, Construction and Services, the Guide ta Enactment of the Model Law